Webinarios para la formación de profesores de Lengua Española en tiempos de pandemia. Un análisis de su presencia y posibilidades - Abio , Gonzalo; Barandela , Ana Margarita; Prates , Luciana Pitwak Machado Silva (Revista (Entre Parênteses), 2022)
This article presents the teaching pedagogical advice realized by the pedagogical sectors of a Brazilian federal university, aiming to report the actions performed in the context of the transition to emergency remote teaching, in 2020, when the Covid-19 pandemic started. Institutionally, teaching pedagogical training was foreseen as a requirement for maintaining the quality of academic activities in a remote regime, and this forecast shows that pedagogical training, the most characteristic function of pedagogical advice, has increased its value in this transitional context. Anchored as a descriptive study, in the light of the theoretical referential of the field of University Pedagogy, it is presented from the sector organization responsible for pedagogical training, through the institutional teacher professional development program, and reaching the actions realized, which culminated in the application of evaluation and research with the institution's professors. The results indicate that the actions have a conception of training that values the movement between theory and reflection on practice, finding an echo in the demands presented by the professors themselves. However, from an analysis of the training model adopted, it shows that the pedagogical sectors need to advance, to contemplate actions that culminate in learning communities, transforming profoundly the institutional pedagogical culture.